Metode Pembentukan Pribadi Muslim Menurut Ali Abdul Halim Mahmud dalam Buku Dakwah Fardiyah - Rakhmawati, Eni (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2023)
Fardiyah da'wah (individual da'wah) is the effort and effort of a da'i towards someone to bring him from darkness to light, from misguidance to guidance, from lack of guidance in life to commitment to the Islamic way of life. In the process, the internalization of noble values such as fardiyah preaching has experienced a decline. This type of research uses qualitative research, with a literary (literary) approach. The primary data is the book "fardiyah preaching" by prof. dr. ali abdul halim Mahmud while the secondary data is a number of literature that is relevant to this thesis but is only supporting in nature, such as: a). books, magazines, newspapers, journals. Data collection techniques researchers use documentation techniques or documentary studies. Data analysis used content analysis, which is a process of interpreting the contents of the message as a whole, either implicitly or explicitly. What is implied is that the text is unclear. While what is meant explicitly is what is stated in the text is clear. The results of the discussion show that the method of forming the Muslim person in the book of fardiyah da'wah by Ali Abdul Halim Mahmud shows us the limits of being observant and careful about the suitability of the terms and adab in fardiyah preaching for da' i, mad'u and da'wah itself. The formation of the Muslim personality in the fardiyah da'wah method, according to the author, is quite successful when applied to the current process of da'wah development which is experiencing many setbacks because in fardiyah da'wah the preachers call on mad'u with words, deeds, exemplary and perfect educational programs, namely the formation of personality. is the main goal of da'i. the emphasis is as a stage until the formation of pious individuals. Individuals who are able to underlie the realization of Islamic society and Muslims.